Peran Pelatihan Dan Digital Marketing Dalam Meningkatkan Kinerja Sumber Daya Manusia di Masa Pandemi Covid-19 Pada Komunitas Umkm Mafia Kuliner Surakarta - CHANDRA, CHANDRA; Ayu Astuti, Aprillia (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
This research aims to find out how the role of training by improving the performance of human resources in an organization or an MSME community in Surakarta. This study measures the level of the role of digital marketing training in improving HR performance as it can increase sales in an organization and MSMEs. The large role of human resources requires companies or MSMEs to be able to optimize the performance of their human resources so that they can make an optimal contribution to the digitalization sector of marketing as an effort to increase income and expand information in the world of technology. Consumer behavior is now born in an era where technology is already in its environment or often called the digital native generation, especially driven by this pandemic, companies or SMEs are also required to be ready to compete. This study uses a quantitative approach method. This type of research data is secondary data, namely data obtained indirectly or through intermediary media in the form of documents or company archives needed in research. The existence of training efforts can cause HR to be able to develop greater duties / obligations and responsibilities and can maximize company profits.